2010
DOI: 10.1590/s1676-06032010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Taxocenose de aves em um remanescente da Floresta com Araucária no Sudeste do Paraná, Brasil

Abstract: Abstract:In this study the community of birds in a small size remnant (10 ha) of Araucária forest, located in the city of Tijucas do Sul, Paraná was evaluated. During the period of November, 1999 to April 2001, 15 surveys had been carried, in which capture with mist nets and visual and aural contacts were used to estimate avian abundance and richness. We recorded 118 species of 35 families. According to the frequency of occurrence around 44% of species were considered with low frequency. When analyzed the trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
1
0
4
Order By: Relevance
“…This pattern seems to be independent of the spatial extent of mixed forests, given that mixed forests form the second largest phytogeographical domain in the state. Previous studies have found that even small mixed forest remnants harbor rich bird assemblages, composed of many species that seem to use edge and forest interior indifferently [ 103 , [ 104 ]. For instance, Araucaria plantations–the dominant tree characterizing mixed forests–house sensitive and endemic birds associated with this forest type [ 105 ], [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern seems to be independent of the spatial extent of mixed forests, given that mixed forests form the second largest phytogeographical domain in the state. Previous studies have found that even small mixed forest remnants harbor rich bird assemblages, composed of many species that seem to use edge and forest interior indifferently [ 103 , [ 104 ]. For instance, Araucaria plantations–the dominant tree characterizing mixed forests–house sensitive and endemic birds associated with this forest type [ 105 ], [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Valores em negrito indicam variáveis com maior influência no eixo de maior significância estatística. rência e abundância relativa de algumas espécies consideradas frugívoras na presente análise, as quais são consideradas sensíveis à fragmentação florestal, sofrendo redução de abundância com ações antrópicas (Anjos, 2004;Cavarzere et al, 2012;Rossi et al, 2014). Além disso, em ambientes modificados, há uma tendência à existência de maior riqueza de espécies onívoras e a uma grande redução nos frugívoros em relação às demais categorias (Weimer et al, 2014;Souza et al, 2014).…”
Section: Resultsunclassified
“…Em sua maioria, os frugívoros registrados têm como habitat o ambiente florestal (n=14), assim como os onívoros (n=12). Esses resultados reforçam a dependência das espécies das três categorias em relação a áreas menos alteradas no fragmento amostrado, porém, demonstrando a suscetibilidade dessas espécies diante de futuros impactos no fragmento florestal, que podem ocasionar uma redução na abundância e na riqueza dessas categorias em longo prazo (Cavarzere et al, 2012). Os dados obtidos indicam que o fragmento florestal estudado está desempenhando um importante papel ecológico no município de São José do Ouro, norte do estado do Rio Grande do Sul, abrigando diversas espécies que direta ou indiretamente dependem do ambiente florestal, devido à sua alta frequência de ocorrência, abundância e estrutura trófica no local.…”
Section: Resultsunclassified
“…esta diferença entre a riqueza estimada e a observada foi de 23 espécies o que representa apenas 9% da riqueza total observada. O número de espécies variou conforme o mês de amostragem (Tabela 1) e as flutuações observadas na composição específica no decorrer dos ciclos sazonais são comumente encontradas em estudos ornitológicos (vide Anjos & Graf 1993, Marterer 1996, Abe 1997, Gimenes & Anjos 2000, Bispo & Scherer-Neto 2010, estando às épocas com maiores riquezas relacionadas com a presença de espécies migratórias e com o período reprodutivo das aves durante a primavera e o verão (Anjos & Graf 1993, Gimenes & Anjos 2000.…”
Section: Resultsunclassified